Determination of Surface Qualities on Inclined Surface Machining with Acoustic Sound Pressure - KURT, MUSTAFA (ASSOC MECHANICAL ENGINEERS TECHNICIANS SLOVENIA, 2012)
Die parts used in automotive and aviation industry have complicated surfaces that require multiaxis machining. In machining of inclined surfaces with ball-end milling, the process is of great significance for its correctness and accuracy. In this study, Acoustic Sound Pressure (ASP) generated during the machining of a workpiece at a vertical machining centre has been measured. The experiments have been conducted in association with cutting velocity, feed rate and step over parameters determined by using different surface forms and different cutter path strategies. Therefore, the aim of this study is to understand the relationships between the generated sound signals and surface roughness in the machining of inclined concave and convex surfaces. In the experiments, the workpiece material of EN X40CrMoV5-1 hot work tool steel, which is commonly used in the related die industry, has been chosen. The ball end mills with two indexable inserts with three different coatings of TiC, TiN, and TiAlN have been used. The results show that there is a rise at the value of surface roughness with a rise at the value of acoustic sound pressure and that surface roughness could be figured out with acoustic sound pressure level.
Keywords: ball end milling; acoustic emission and sound pressure; linear regression; surface roughness; EMISSION SIGNALS; TOOL WEAR; MALFUNCTIONS; SENSOR; FORCE